Nervous Necrosis Virus Replicates Following the Embryo Development and Dual Infection with Iridovirus at Juvenile Stage in Grouper - Kuo, Hsiao-Che; Wang, Ting-Yu; Hsu, Hao-Hsuan; Chen, Peng-Peng; Lee, Szu-Hsien; Chen, Young-Mao; Tsai, Tieh-Jung; Wang, Chien-Kai; Ku, Hsiao-Tung; Lee, Gwo-Bin; Chen, Tzong-Yueh (PLOS ONE, 2012)
Infection of virus (such as nodavirus and iridovirus) and bacteria (such as Vibrio anguillarum) in farmed grouper has been widely reported and caused large economic losses to Taiwanese fish aquaculture industry since 1979. The multiplex assay was used to detect dual viral infection and showed that only nervous necrosis virus (NNV) can be detected till the end of experiments (100% mortality) once it appeared. In addition, iridovirus can be detected in a certain period of rearing. The results of real-time PCR and in situ PCR indicated that NNV, in fact, was not on the surface of the eggs but present in the embryo, which can continue to replicate during the embryo development. The virus may be vertically transmitted by packing into eggs during egg development (formation) or delivering into eggs by sperm during fertilization. The ozone treatment of eggs may fail to remove the virus, so a new strategy to prevent NNV is needed.